With great power comes great responsibility: inquiry into the social roles and the power dynamics in human-AI interactions. Issue 3 (3rd July 2022) - Hong, Joo-Wha
Abstract : As machines are becoming more interactive, such as Artificial Intelligence (AI) agents, the importance of interactions between humans and AI increases as a new type of communication. However, unlike most studies have examined the influence of AI on individuals, fewer studies about how human-AI interactions will impact society have been conducted. It should be acknowledged that we attribute social roles to AI when assigning social tasks, and there are power dynamics within an interaction between humans and AI because of it. Also, we should ask whether the current society is ready for AI to take responsibility for its actions. Finally, limitations on existing human-machine communication (HMC) studies, an unclear definition of AI as an interlocutor and a lack of theoretical frameworks, were pointed out with suggestions. It is expected that considering a machine's social roles and powers in human-AI interactions will broaden the theoretical realm of HMC.